2000
DOI: 10.1002/(sici)1521-186x(200005)21:4<287::aid-bem5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency magnetic fields can either increase or decrease analgaesia in the land snail depending on field and light conditions

Abstract: Results of prior investigations with opioid peptide mediated antinociception or analgaesia have suggested that these extremely low frequency (ELF) magnetic field effects are described by a resonance mechanism rather than mechanisms based on either induced currents or magnetite. Here we show that ELF magnetic fields (141–414 μT peak) can, in a manner consistent with the predictions of Lednev's parametric resonance model (PRM) for the calcium ion, either (i) reduce, (ii) have no effect on, or (iii) increase endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 64 publications
(116 reference statements)
5
52
0
Order By: Relevance
“…As the initial exposures to the shielded environment were in the dark but during the mid-light phase of the diurnal cycle, we reintroduced white light into the shielded environment and the analgesic effect was eliminated. We have shown (Prato et al 2000), as have others (Betancur et al 1994), that light modulates the effects of the applied magnetic fields on the attenuation of opioid/ opiate-induced analgesia in snails and mice. In all these experiments, the applied magnetic fields were either static or time changing (generally less than 300 Hz) and considerably greater than the ambient magnetic fields.…”
Section: Introductionsupporting
confidence: 70%
“…As the initial exposures to the shielded environment were in the dark but during the mid-light phase of the diurnal cycle, we reintroduced white light into the shielded environment and the analgesic effect was eliminated. We have shown (Prato et al 2000), as have others (Betancur et al 1994), that light modulates the effects of the applied magnetic fields on the attenuation of opioid/ opiate-induced analgesia in snails and mice. In all these experiments, the applied magnetic fields were either static or time changing (generally less than 300 Hz) and considerably greater than the ambient magnetic fields.…”
Section: Introductionsupporting
confidence: 70%
“…Attenuation of pulsed magnetic field-induced analgesia by naloxone, an opioid antagonist, as well as by mu and delta opioid receptor antagonists, provides further support for the role of opioids in the mediation of such analgesia [33,34]. Furthermore, these effects were dependent on the presence of light, and were not present in the absence of light [35]. Additionally, Galic and Persinger [36] examined whether geomagnetic disturbances are associated with pain thresholds by exposing adult mice to a hotplate paradigm once weekly for 52 weeks during the dark cycle.…”
Section: Discussionmentioning
confidence: 77%
“…Magnetic fields have been proposed to alter the proprieties and stability of biological membranes, their transport characteristics, and the intra-and extracellular distribution and flux of calcium ions. Results of a number of investigations have shown that the inhibitory effects of magnetic fields on opioid analgesia in snails involve alterations in the functioning of calcium and/or flux of calcium ions , 1991 consistent with a resonance model (Prato et al 1995), as well as alterations in protein kinase C-associated and nitric oxide and nitric oxide synthase-related transduction mechanisms Kavaliers & Prato 1999;Prato et al 2000). The absence of magnetic field influencing biological systems following similar mechanisms remains to be determined, although Lednev et al (1996) suggested that effects seen at near-zero (vector-nulled) magnetic field conditions are related to the parametric resonance model.…”
Section: Discussionmentioning
confidence: 87%